Editorial (2019)
The 51st edition of the Semestre Económico journal is composed by seven articles in which topics belonging to the research fields defined in the scope of the journal are presented, such as economic development, regional development and competitiveness; environmental economics and sustainability; Microeconomic aspects referred to conceptual elements that must be taken into account when analyzing different markets, as well as the study of macroeconomic aggregates and public sector economy. Of the seven articles presented in this issue, four result from research and three from literature reviews. These were written by ten authors, six from Colombia, two from Argentina, one from Peru and one from Spain.